Filipino consumers' understanding and use of nutrition labels - Baliclic, Micah Fiel Calaranan; Francisco, Maria Leonora dL. (Quezon City College of Home Economics, University of the Philippines Dilman, 2015)
Different risk factors in the lifestyle of consumers including unhealthy diet were blamed for the increasing number of noncommunicable diseases, overweight, and obesity cases over the last two decades in the Philippines. This has been counteracted by national efforts to promote healthy dietary practices; one of which is the formation of consciousness towards nutrition labeling in food packages. The study was conducted to explore the knowledge, attitude, and practices on nutrition labelling of Filipino consumers and assess the effectiveness of different nutrition label formats in helping them make healthy food choices. It was administered through a face-to-face interview with 100 mothers in Caloocan, Philippines, who shared a major responsibility in household food purchase. Findings revealed that there was widespread awareness of nutrition and its importance to food purchase and dietary practices. Seventy-nine percent and 69% of the respondents claimed to be knowledgeable about health and nutrition issues and were influenced by nutrient content when purchasing a food product, respectively. However, this awareness was not reflected on the respondents' frequency of reading nutrition labels and knowledge on its technical aspect such as nutrient terminologies and numerical expressions. Only 38% were reading nutrition labels on a regular basis and the mean score of the respondents on a 5-item test about nutrition label-reading was 2.21±0.90. Results further showed that the respondents had varying responses to the five nutrition label formats presented, namely Guideline Daily Amounts for energy, health logo, Guideline Daily Amounts for energy plus health logo, Nutrition Facts table, and traffic light. Front-of-pack labels generally obtained higher ratings than the traditional nutrition table in terms of preference, credibility, and ease of understanding. Despite the differences in said measures, food products which display varying nutrition labels were not perceived by the respondents as significantly healthier than the other. The comparative processing of nutrition information was found to be more accurate using health logo in 98% of the respondents and more rapid using GDA plus health logo in 45% of the respondents. Results also indicated that the addition of health logo and traffic light on food packages would cause majority of the respondents to increase their purchase (93% for health logo and 70% for traffic light) and consumption (59% for health logo and 51% for traffic light) of the products that exhibit such nutrition labels.
Thesis (BS Food Technology)--University of the Philippines Diliman
Keywords: Food -- labeling -- Philippines; Consumers -- Philippines